Prognostic Value of Ultrasound Stratigraphy in Long-Term Weight Loss: Results from a Nutritional Counseling Program - De Toni, Luca (Obes Facts, 2019)
BACKGROUND: Weight control through lifestyle interventions represents a suitable strategy to avoid the metabolic, endocrine, and reproductive comorbidities associated with overweight and obesity. Reduced testosterone (T) levels are a worsening factor in overweight males. However, prognostic parameters of long-term weight loss are not readily available. Here, we tested the prognostic value of early variations of anthropometric and hormonal parameters, with a focus on ultrasound stratigraphy (US) and the reduction in body mass index (BMI) associated with nutritional counseling/lifestyle interventions at 6-month follow-up. METHODS: Ninety-five male subjects (BMI 25–34.9 kg/m2) who had undergone nutritional/lifestyle interventions, were retrospectively analyzed for: body weight and composition; US evaluation at the triceps (TRC), abdominal (ABD), and thigh (THI) areas; and circulating levels of T, luteinizing hormone, and follicle-stimulating hormone. Sixty patients (63.2%) completed the 6-month follow-up program. RESULTS: At 6 months, a significant reduction in BMI (26.38 ± 1.55 vs. 31.5 ± 5.0 basal, p < 0.001) and increase in T levels (18 ± 5.4 vs. 9.5 ± 2.3 nmol/L basal, p = 0.04) were observed. Subjects in the highest quartile of the BMI reduction at 6 months (ΔBMI 6 mo), compared to the lowest, showed a significant difference at the 2-month follow-up variation of BMI (p = 0.025), and fat and muscle thickness at the TRC (both p < 0.001) and ABD (p < 0.001 and p = 0.002, respectively) areas. Variation of TRC muscle thickness at 2 months was the only independent predictor of ΔBMI 6 mo in the multiple stepwise regression analysis. CONCLUSIONS: BMI evaluation and US represent useful monitoring tools in the follow-up of nutritional/lifestyle interventions for overweight-to-mildly obese patients. The important effects on motivation and adherence to the intervention program are to be considered.